Experimental study on the thermal conductivity and viscosity of transformer oil -based nanofluid containing ZnO nanoparticles - Mojtaba Parvar; Syfolah Saedodin; Seyed Hadi Rostamian (Journal of Heat and Mass Transfer Research, 2020)
This study investigates the effect of ZnO nanoparticles to transformer oil on the thermal conductivity and dynamic viscosity. The consequence of the temperature and nanofluid concentration as an important parameters have been explored on the thermal conductivity and viscosity of the samples. The results indicated that the thermal conductivity of the nanofluid was higher than that of the pure transformer oil at the temperature of 25°C. Also, a rise in the nanoparticle concentration of transformer oil increased the thermal conductivity of nanofluid. Besides, the thermal conductivity at the volume fractions of 0.05% and 1% increased by approximately 4.61% and 11.53%, respectively. The dynamic viscosity reached the highest level at maximum volume fraction in all temperatures. In addition, an increase in the temperature reduced the dynamic viscosity of both the pure transformer oil and the nano-oil. At a given temperature, a rise in the volume fraction of ZnO nanoparticles enhanced the dynamic viscosity. Moreover, to predict the dynamic viscosity of nanofluid, a new correlation has been presented as a function of temperature and volume fraction with R-Sq=0.9913.